2018
DOI: 10.1186/s12890-018-0699-0
|View full text |Cite
|
Sign up to set email alerts
|

Real-world treatment patterns for patients 80 years and older with early lung cancer: a nationwide claims study

Abstract: BackgroundOld age is an important factor that could affect the treatment of early-stage lung cancer. In this study, we evaluated the treatment patterns and outcomes of patients over the age of 80 years who had been diagnosed with early-stage lung cancer in real-world practice.MethodsElderly patients who were diagnosed with early-stage lung cancer between 2008 and 2016 were identified using claims data provided by the Health Insurance Review and Assessment Service. The proportion of patients who underwent surgi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Local therapies as definitive treatment of these lesions is among the standard managements, especially in patients with surgical contraindications, for instance prohibitive cardiorespiratory risks or inadequate lung function. Among patients newly diagnosed with early stage lung cancer, 5-10% have absolute or relative contraindications to surgery (2,3), but the percentage could be as high as 28% in octogenarians (4). Treatment modalities such as stereotactic body radiation therapy (SBRT) (5), percutaneous ablation techniques for instance radiofrequency (RFA) (6), microwave (MWA) (7) and cryotherapy (8) are highly effective and are associated with reasonable local control rates ranging from 64% to 69.8% at 2 years.…”
Section: Introductionmentioning
confidence: 99%
“…Local therapies as definitive treatment of these lesions is among the standard managements, especially in patients with surgical contraindications, for instance prohibitive cardiorespiratory risks or inadequate lung function. Among patients newly diagnosed with early stage lung cancer, 5-10% have absolute or relative contraindications to surgery (2,3), but the percentage could be as high as 28% in octogenarians (4). Treatment modalities such as stereotactic body radiation therapy (SBRT) (5), percutaneous ablation techniques for instance radiofrequency (RFA) (6), microwave (MWA) (7) and cryotherapy (8) are highly effective and are associated with reasonable local control rates ranging from 64% to 69.8% at 2 years.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, SBRT may be beneficial in elderly patients. According to a national survey in South Korea, the percentage of patients aged ≥ 80 years receiving SBRT as a treatment modality for early NSCLC increased from 9.4% in 2008 to 28.6% in 2016 [ 12 ]. While some studies have revealed that SBRT is an effective and safe treatment modality in elderly patients aged ≥ 80 years [ 13 15 ], most studies included patients who were not pathologically confirmed to have NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…After SBRT, QoL was maintained, and emotional functioning was improved, whereas QoL worsened after surgery (86). Several studies report similar findings regarding the better or comparable outcomes of SBRT against surgery in elderly patients with NSCLC (87)(88)(89)(90)(91)(92).…”
Section: Rt In the Elderlymentioning
confidence: 77%